FAKTOR PENYEBAB DAN IMPLIKASI YURIDIS PENGUNDURAN DIRI PANITIA PEMILIHAN KEPALA DESA MAHAL KECAMATAN OMESURI KABUPATEN LEMBATA - Mole, Mathias; Tuan, Yohanes; Asnawi, Norani (Petitum Law Journal, 2024)
One important aspect in the process of realizing simultaneous Village Head elections is the role of relevant institutions in carrying out Village Head elections. The institution referred to is the village head election committee at the village level. The election for the head of Mahal Village was marked by the resignation of the village head election committee. This research aims to find out the factors causing the resignation of the village head election committee and to find out the legal implications of the resignation of the election committee. Empirical legal research is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The research results show that the resignation of the Mahal village election committee was caused by internal and external factors. Internal factors include: differences in perception regarding proof of immoral customary acts, deemed not comprehensive in carrying out the requirements research stage, the time limit for immoral acts is under the five years limit, not showing evidence of an open statement of not committing immoral acts, weak supervision by the village head election supervisory team. , does not impose administrative sanctions on prospective candidates suspected of committing immoral acts, threats from BPD Mahal and refusal to sign minutes, and resignation of candidates suspected of committing immoral acts. External factors include the absence of factual verification by the district, a vote of no confidence from the public, no guarantee of comfort for the election committee and their families and pressure from the victim. The juridical implications of the resignation of the Mahal village election committee include: the vacancy of the Mahal village head election committee, the phenomenon of a legal vacuum, the postponement of village head election activities at a later stage, and the formation of a new (replacement) election committee. The mechanism for the resignation of the village head election committee is not expressly included in the legal basis for the technical instructions for village head election. The Mahal Village Consultative Body formed a new (replacement) election committee based on instructions from the district level election committee with letter number B.U140/2031/Dinas PMD/X/2021 to carry out duties and responsibilities at the next stage.